1990
DOI: 10.1111/j.1476-5381.1990.tb15794.x
|View full text |Cite
|
Sign up to set email alerts
|

The actions of adenosine 5′‐triphosphate on guinea‐pig intracardiac neurones in culture

Abstract: 1 The actions of adenosine 5'-triphosphate (ATP) and related nucleotides and nucleosides on the membrane ion conductances of M and AH type intracardiac neurones cultured from ganglia within the atria and interatrial septum of newborn guinea-pig heart were studied with intracellular current- 3 In 41% of M and 43% of AH type cells, focal application of ATP (500pM) evoked rapid depolarization with an increase in conductance which frequently elicited action potential discharge. The underlying inward current had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…Outside of the CNS, purinoceptor mediated responses have been detected with a profile of agonist potency similar to that of P2X 4 [27]. P2X 4 message was found to be widely expressed throughout many different tissues; thus the P2X4 subtype appears to be the most widespread member of the P2X family.…”
Section: Discussionmentioning
confidence: 89%
“…Outside of the CNS, purinoceptor mediated responses have been detected with a profile of agonist potency similar to that of P2X 4 [27]. P2X 4 message was found to be widely expressed throughout many different tissues; thus the P2X4 subtype appears to be the most widespread member of the P2X family.…”
Section: Discussionmentioning
confidence: 89%
“…Although several other workers have shown that ATP excites neurones grown in culture from parasympathetic cardiac ganglia (Allen & Burnstock, 1990;Fieber & Adams, 1991) and nodose ganglia (Krishtal et al, 1988a,b) this is, as far as we know, the first demonstration of a depolarizing effect of this agent on whole vagal nerve trunks. The depolarizing action of ATP was marked but high concentrations were necessary.…”
Section: Discussionmentioning
confidence: 97%
“…From the relative order of potencies of a series of ATP analogues, the predominant effect is mediated by a receptor which appears to be a P2X, receptor. Interestingly, from patch-and voltage-clamp studies on neurones cultured from parasympathetic intracardiac ganglia it appears that the excitatory effects of purines are mediated via a receptor that shares more similarities with the P2y than the P2, purinoceptor (Allen & Burnstock, 1990;Fieber & Adams, 1991). It remains to be established whether there is a genuine difference in the purine receptor population on the intracardiac neurones and on the axonal membranes of the cervical vagal nerve trunk or whether these contrasting findings can be attributed to the different methods used to study these receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These currents were, however, insensitive to the muscarinic receptor antagonists, pirenzepine and atropine (data not shown) and thus constitute a nicotinic AChR-mediated current. An ATP-induced current has also been described in parasympathetic neurones of mammalian intracarditc ganglia (Allen & Burnstock, 1990b;Fieber & Adams, 1991b)`i However, ATP-evoked currents were unaffected Ity bath application of either 1I00 jiM potential. This voltage sensitivity suggests that QX-222 binds at a site within the electric field, presumably the pore-forming region, of the ACh receptor-channel in parasympathetic neurones.…”
Section: Single-channel Recordingsmentioning
confidence: 99%